Analysis of the Effect of Self-Regulation and Adversity Quotient on Resilience and Its Implications on the Psychological Well-Being of Islamic Religious Education Teachers - Ichsan Ichsan; Sedya Santosa; Muhammad Ghozil Aulia; Ikhsan Rifai; Nur Munajat (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study investigates the influence of self-regulation and adversity quotient on resilience and examines their implications for the psychological well-being of Islamic Religious Education (IRE) teachers. A quantitative, predictive correlational design was employed. Data were collected using a structured questionnaire that incorporated validated scales measuring self-regulation, resilience, and psychological well-being. Path analysis was conducted using JAMOVI software with a robust model. The results indicate that self-regulation positively and significantly affects resilience, while resilience, in turn, positively influences psychological well-being. Moreover, both self-regulation and adversity quotient were found to have direct positive effects on psychological well-being. The analysis further revealed indirect effects of self-regulation on psychological well-being mediated by resilience. These findings highlight the importance of strengthening self-regulation and resilience among IRE teachers to enhance their overall psychological well-being.